Odpowiedzi

2009-11-29T18:40:48+01:00
A) -4x-7-3x+7=-7x
b) x-2xy+1/2x-1/3 =1½x-2xy-1/3
c) -x² + y² -2x² -2y²=-3x²-y²
d) -x² +2x-3x+x²=-x
e) 4x+4-7x-½=-3x+3½
f) -2ab+12a-4ab-16a=-6ab-4a
2009-11-29T18:42:21+01:00
A) -4x-7-3x+7 = -7x
b) x-2xy+1/2x-1/3 = 1i1/2x -2xy -1/3
c) -x ^ + y ^ -2x ^ -2y ^ = - 3x^ - y^ ^-oznacza kwadrat)
d) -x ^+2x-3x+x ^ = -x
e) 4x+4-7x-1/2 = -3x + 3 i 1/2
f) -2ab+12a-4ab-16a = - 4a - 6ab
2009-11-29T18:42:38+01:00
A) -7x
b) 1/2x(kwadrat) -2xy - 1/3
c)-3x(kwadrat)- y kwadrat
d) -x
e)-3 +7/2
f)-6ab-4a